7(6x-5)+15x=

Simple and best practice solution for 7(6x-5)+15x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6x-5)+15x= equation:


Simplifying
7(6x + -5) + 15x = 0

Reorder the terms:
7(-5 + 6x) + 15x = 0
(-5 * 7 + 6x * 7) + 15x = 0
(-35 + 42x) + 15x = 0

Combine like terms: 42x + 15x = 57x
-35 + 57x = 0

Solving
-35 + 57x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '35' to each side of the equation.
-35 + 35 + 57x = 0 + 35

Combine like terms: -35 + 35 = 0
0 + 57x = 0 + 35
57x = 0 + 35

Combine like terms: 0 + 35 = 35
57x = 35

Divide each side by '57'.
x = 0.6140350877

Simplifying
x = 0.6140350877

See similar equations:

| 2l+2(70)=800 | | -9/7=-2x-x | | x-6=x-9 | | (w-5)(w+5)= | | 8=-5t-2 | | 4=3x/4-2 | | -2/x | | -125/x=-21 | | 6(2x+3)=24 | | -6u-30=0 | | 3z^2-10z+3=0 | | 4t+12=0 | | -0.75x-47.77=-27.27-4.85x | | 1-1/4 | | 4z^2-4z-48=0 | | -2-(-3)-3= | | 1/2-2/1+3/4 | | 8+x-8+2+6+x-4= | | 2n-4(n-6)=1/2(-4n-5) | | 6t-20=-8 | | n^3-20n^2-5=0 | | 5(3b-3)-3(3b-7)=12 | | 6x^2+-7x^2= | | -14=-8u+15 | | -0.5t-3.7=-0.7 | | x+55.5=-x-44.5 | | 35000-8t=0 | | x+555=-x-445 | | x^3-17x^2-3x-9=0 | | 0.6x-1=2.2x-25 | | 5-0*3+9/3 | | (9h-11k)(9h-11k)= |

Equations solver categories